KOMUNIKASI DESTINATION BRANDING LEREH LEREH BWI 1 TV DALAM MEMBENTUK IDENTITAS DAERAH - Moch. Nuril Anwar; Mariyatul Qiptiyah; Siti Holiza Fitriana; Fasya Rina Sitajeng; Inayatul Maghfiroh (Fakultas Dakwah Universitas Ibrahimy, 2026)
This research aims to analyze the strategy of the